2021
DOI: 10.1038/s41598-020-79479-5
|View full text |Cite
|
Sign up to set email alerts
|

The potential ameliorative impacts of cerium oxide nanoparticles against fipronil-induced hepatic steatosis

Abstract: Fipronil (FIP) is a phenylpyrazole insecticide that is commonly used in agricultural and veterinary fields for controlling a wide range of insects, but it is a strong environmentally toxic substance. Exposure to FIP has been reported to increase the hepatic fat accumulation through altered lipid metabolism, which ultimately can contribute to nonalcoholic fatty liver disease (NAFLD) development. The present study aimed to examine the function of cerium oxide nanoparticles (CeNPs) in protecting against hepatotox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 82 publications
2
23
0
Order By: Relevance
“…The oral administration of CeO 2 NPs (<25 nm) also protected albino rats against hepatotoxicity induced by fipronil. The effects included reduction in the hepatic levels of MDA and nitric oxide, and also an improvement in the hepatic activities of glutathione peroxidase and superoxide dismutase [ 86 ].…”
Section: Fatty Liver Diseasementioning
confidence: 99%
“…The oral administration of CeO 2 NPs (<25 nm) also protected albino rats against hepatotoxicity induced by fipronil. The effects included reduction in the hepatic levels of MDA and nitric oxide, and also an improvement in the hepatic activities of glutathione peroxidase and superoxide dismutase [ 86 ].…”
Section: Fatty Liver Diseasementioning
confidence: 99%
“…In vivo tests have confirmed the in vitro observation and showed that fipronil is a risk factor in vertebrate reproduction [86]. The long-term exposure to toxic agrochemicals causes bioaccumulation of fatty acid in hepatic cells, leading to fibrosis and hepatitis [87]. The accumulation of ROS has a critical role in the hepatic and is responsible for inflammation in the liver cause hepatic tissue injuries [88].…”
Section: Nanocarriers and Toxicity Of Pesticidesmentioning
confidence: 79%
“…A study to examine the beneficial impact of fipronil-cerium oxide nanoparticles on hepatic tissue was evaluated in vivo. The results proved that cerium oxide nanoparticles had avoided the inflammation process in rats' blood, reducing the bioaccumulation of fatty acids and reducing liver damage [87].…”
Section: Potential Ameliorative Impact Of Nanoparticlesmentioning
confidence: 85%
“…Most of the reviewed studies have reported the ability of CeO 2 NPs to reduce hepatic fibrosis/steatosis, alleviate hepatocellular damage, restore liver tissue architecture, normalize portal pressure, enhance hepatocytic regeneration, and among many others. Different laboratory biomarkers were used to prove the therapeutic/prophylactic impact of CeO 2 NPs, such as alanine aminotransferase (ALT), aspartate aminotransferase (AST), lactate dehydrogenase (LDH) and bilirubin 9,42,43,46,47 In addition, indicators for lipid peroxidation (e.g., MDA and NO) and antioxidant enzymes (e.g., glutathione and SOD) were also used to verify the mechanism of improvement seen on the histological level 45,47,48 …”
Section: Protective/therapeutic Role Of Ceo2nps In Liver Disordersmentioning
confidence: 99%
“…• Reduced serum alphaprotein levels. (Continues) also used to verify the mechanism of improvement seen on the histological level 45,47,48 In terms of hepatic steatosis, most findings demonstrated that attenuation of pathological lipid peroxidation, after the administration of CeO 2 NPs, has reduced the damaging influence of ROS on the liver tissue. CeO 2 NPs were also found to prevent/reduce steatosis by interfering with the adipogenic pathway by reducing the transcription of genes involved in adipogenesis, and by hindering lipid accumulation in hepatocytes.…”
Section: Protective/therapeutic Role Of Ceo Nps In Liver Disordersmentioning
confidence: 99%